Monetary Implication of Environmental Disamenities on Housing Investment in Lagos State: The Ojota Scenerio - Akinjare, O. A (Mediterranean Journal of Social Sciences, 2011)
Numerous studies have ascertained the diminutionary tendencies of disamenities such as solid waste landfills on real estateinvestments despite previous mixed conclusions. This study examines one of the four landfills in Lagos State- Olusosun landfill locatedin Ojota, Lagos and its estimated financial implication on the real estate market in Lagos State, Nigeria. A relational distance of 1200m radius was established between the landfill and residential properties by which property values were measured based on consistentintervals of 300meters up to 1 200 meters in concentric rings. The study indicated within the Olusosun landfill neighbourhood, anincrease in property values were evident as distance away from the landfills increased indicating that residential houses in close proximityto the landfills suffered value loss. Property appreciation relative to distance averaged 6% within the concentric rings of the landfill whilethe an estimated total loss on the real estate market via the landfill found to be approximately =N=2.1billion. The study recommendedthat if improved technology could not be utilised in the effective management of the various sanitary landfills within developed areas of thestate, the current landfills in operation be closed down and relocated to the outskirts of the city to forestall a consistent appreciation in realestate investment in the state.